Perdebatan Penerapan Pembuktian Terbalik dalam Perkara Tindak Pidana Korupsi - Mancur Sinaga; Maidin Gultom; Ica Carina; Sahata Manalu (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2026)
This study examines the debate over the application of reverse burden of proof in corruption cases in Indonesia. The issue is significant because reverse burden of proof lies at the intersection between the need for effective corruption eradication and the protection of fundamental principles of fair criminal justice. This study employs normative legal research using statutory, conceptual, and analytical approaches. The primary legal materials include the Corruption Eradication Law and its amendment, the National Criminal Code, the Criminal Procedure Code, and relevant international legal instruments. The findings indicate that reverse burden of proof in corruption cases cannot be understood as an absolute reversal of the burden of proof. This mechanism applies mainly in a limited manner to gratification, the origin of the defendant’s assets, and property suspected of deriving from corruption. The main debate concerns the risk of shifting the burden of proof from the public prosecutor to the defendant when reverse burden of proof is applied broadly without clear limitations. Therefore, reverse burden of proof must be constructed as a special mechanism that is limited, balanced, proportional, and subject to judicial control during trial proceedings. This study concludes that reverse burden of proof may be maintained as an instrument for corruption eradication as long as it does not eliminate the prosecutor’s obligation to prove the indictment and does not disregard the rights of the defendant.